Decision Support System Selection Cocoa Seed Using Web-Based AHP Hybrid WP Method - Andarias Liku; Muslimin B; Yuanita Yuanita (Politeknik Pertanian Negeri Samarinda, 2020)
Cocoa Plant (Theobroma cacao L) is one of the plantation commodities that has an important role in the Indonesian economy. One of the cocoa-producing regions in Indonesia is East Kalimantan, the expanse of land in KALTIM Province is still a lot that is not optimally cultivated so that if utilized for cocoa crops, it will have a positive impact on the regional economy. The first step that should be taken by cocoa farmers is the need to use superior cocoa planting materials (seeds). But in cocoa seed selection there are still many who use manual systems so that this kind of thing takes a long time and is less efficient, so a system is needed that is the System supporting cocoa seed selection decisions using AHP hybrid WP method based on the web. This aims to make it easier for cocoa farmers to efficiently select cocoa seeds. This study aims to calculate and create a system that can manage cocoa seed selection by applying modeling of hybrid WP AHP method that can be accessed by many people. The method used is the AHP Hybrid WP Method which is the merging of two methods namely the AHP method and the WP method. The AHP method is used to evaluate the weight value of the criteria, while the WP method is used to evaluate alternative values so that the two methods get a ranking decision. This application can calculate and process cocoa seedlings to produce the best cocoa seed sequence and accessible to many in need.